A new biomimetic antifouling method based on water jet for marine structures. (May 2020) - Liu, Guijie; Yuan, Zichao; Incecik, Atilla; Leng, Dingxin; Wang, Shuai; Li, Zhixiong
Marine biofouling is a serious environmental problem, while traditional chemical antifouling is less environmentally friendly. Biomimetic antifouling is able to overcome this issue by restraining the growth of biofouling at the very beginning, while the current research interest in this field focuses on the dynamic antifouling layers. In order to construct a flowing layer on the surfaces of marine structures such as a ship hull, this study proposes a new biomimetic antifouling method based on the water jet. This new method is inspired by the antifouling mechanism of the kelp and attempts to generate a flowing jet layer on the surface of the marine structure by spraying the water outward. The fouling organism cannot find enough attachment points on the surface of the marine structure because the flow force is greater than adhesion. In order to optimize the design of the water jet, attachment point theory was used to analyze the effect of jet velocity on the flow force, and numerical simulation was conducted to investigate the distribution of the water jet. Based on the theoretical analysis results, experimental tests were carried out to evaluate the performance of the proposed antifouling method. The results demonstrated that the adhesion amount of Phaeodactylum tricornutum can be effectively reduced. The proposed method is able to prevent the attachment of unicellular fouling organisms, thereby hindering the entire fouling process.